Understanding Restorative Justice : How Empathy Can Close the Gap Created by Crime - Wallis, Pete (Book collections on Project MUSE., 2014)
This unique book is a clear and detailed introduction that analyses how restorative justice nurtures empathy, exploring key themes such as responsibility, shame, forgiveness and closure. Using case studies, the book offers a fresh angle on a topic that is of growing interest both in the UK and internationally.